2022
DOI: 10.1140/epjc/s10052-022-10971-0
|View full text |Cite
|
Sign up to set email alerts
|

Testing Born–Infeld f(T) teleparallel gravity through Sgr $$\hbox {A}^\star $$ observations

Abstract: We use observational data from the S2 star orbiting around the Galactic Center to constrain a black hole solution of extended teleparallel gravity models. Subsequently, we construct the shadow images of Sgr $$\hbox {A}^{\star }$$ A ⋆ black hole. In particular, we constrain the parameter $$\alpha =1/\lambda $$ α = 1 / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 166 publications
0
7
0
Order By: Relevance
“…In principle, such a a violation of MSS bound in f (T ) teleparallel gravity could be tested in forthcoming BH shadow and GW detections. Phenomenology and possible matching with observational data, see for example [31], will be the argument of a forthcoming study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, such a a violation of MSS bound in f (T ) teleparallel gravity could be tested in forthcoming BH shadow and GW detections. Phenomenology and possible matching with observational data, see for example [31], will be the argument of a forthcoming study.…”
Section: Discussionmentioning
confidence: 99%
“…1 See Refs. [25][26][27][28][29][30][31][32][33] for several recent works on BH shadow and QNMs beyond GR.…”
Section: Dynamical Horizon In F (T ) Gravitymentioning
confidence: 99%
“…Further, we aim to evalute the effect of the plasma medium on the optical images of the RGI BH. To achieve this goal, we use the backward raytracing technique [50,[63][64][65][66][67][68]. In this technique, for the given image, one has to compute the specific intensity, , observed at some distance from the BH [64] {γ, Ω} Fig.…”
Section: ν0mentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47][48]. More recently, new observations made by the EHT team on the shadow of the Sgr A BH [49] have also spurred interest in further analytical studies on BH and wormhole shadow models [50][51][52][53][54][55][56].…”
Section: Introduction R −Nmentioning
confidence: 99%
“…BHs can be characterized by various features, including a photon sphere radius consisting of orbiting light rays. Additionally, light rays can be categorized as unstable or stable based on whether they can fall or escape to infinity, respectively [11,12]. The astronomical survey carried out by the Event Horizon Telescope (EHT) team revealed that the bright accretion disk encircling the SMBH M87 appears distorted, which is believed to be caused by the phenomenon of GL.…”
Section: Introductionmentioning
confidence: 99%